DISEASE PERCEPTION AND HEALTH SEEKING BEHAVIOUR AMONG HALBA OF CHHATTISGARH - Dr. Sampada Bais Kashyap,; Ms. Subhi lakhera, (IJRDO - Journal of Social Science and Humanities Research, 2024)
Chhattisgarh is tribal dominated State. Tribes constitute approximately 31.5% part of total state population. There is around 42 types of tribe and 5 PVTGs in Chhattisgarh (Census of C.G., 2011). Tribe’s habitat and daily life need depend upon forest, not only economically, but they are show socio-cultural association with forest. Health seeking behavior among tribals influence by some common belief, practices and culture. The present study is conducted among Halba tribes of Chhattisgarh